An evaluation of value-based outcomes for women admitted to a dialectical behaviour therapy integrated practice unit: a follow-up study. Issue 1 (28th January 2023) - Webb, Elanor Lucy; Girardi, Alessandra; Fox, Emily; Wallang, Paul
Abstract: Background: An earlier evaluation (Fox et al ., 2014 ) highlighted reductions in risk behaviours and restrictive practices for women admitted to low secure dialectical behaviour therapy (DBT) unit. Since then, a value-based healthcare model has been adopted. Aims: To explore changes in health, social and psychological functioning, risk, quality of life, and in incidents of violence and restrictive practices, over the initial 12-month period of admission to a specialist DBT service. Method: Data were extracted from electronic clinical records for 41 women with emotionally unstable personality disorder admitted to a specialist integrated practice unit (IPU) providing a comprehensive DBT programme. Secondary analysis was conducted on an anonymous dataset of routinely collected outcome measures at baseline admission, and 6 and 12 months post-admission. ANOVAs and pairwise post hoc comparisons, and non-parametric equivalents, were conducted to examine changes in outcomes. Results: Findings showed statistically significant improvements in mental health scores on the ReQOL ( p <.01), global, wellbeing, problems, functioning and risk scores on the COREOM (all p <.01), and severe disturbance, emotional wellbeing, socioeconomic status, risk and need scores on the HoNOS-Secure (all p <.05). Significant reductions in risk behaviours ( p <.01) and restrictive practices ( p <.01) were also apparent. The most substantiative improvements were largely demonstrated over a 12-month admission period. Conclusions: Admission to the DBT IPU yielded significant improvements on outcomes pertaining to quality of life, psychological distress, and risk. Importantly, these are outcomes that aligned with patients' perceptions of recovery.